Construir región y paz (2021)
The article refers to the collaborative and communal construction of development and peace programs in the region of Magdalena Medio. This construction starts from the concept of human dignity from the conviction that each one of us is a manifestation of the mystery of God and that we exist because we are loved by God forever. In the article is shown how in Magdalena Medio with the effort and the participation of all the citizens and inhabitants of the region some scenarios of commitment and coexistence have been constructed, based on the recognition of every and each one of their acts, their will to contribute in the creation of options for the coexistence. Some humanitarian spaces have been created in the region where the community leaders lead processes of civil sovereignty to face the armed groups. The peace and development program of Magdalena Medio is a productive Project where people identify and construct the way in which they want to live. People construct conditions to establish production relations where the human dignity is not hurt. Alternative projects are proposed to face the forms promoted by the agents of violence. The process of Magdalena Medio is a very complex process which requires the Interdisciplinary contribution and the solidarity of many institutions and many courageous people with humanitarian values to assume the risks that these efforts have.